Consequences of changing Canadian activity patterns since the COVID-19 pandemic include increased residential radon gas exposure for younger people - Natasha L. Cholowsky; Myra J. Chen; Ghozllane Selouani; Sophie C. Pett; Dustin D. Pearson; John M. Danforth; Shelby Fenton; Ela Rydz; Matthew J. Diteljan; Cheryl E. Peters; Aaron A. Goodarzi (Scientific Reports, 2023)
Abstract The COVID-19 pandemic has produced widespread behaviour changes that shifted how people split their time between different environments, altering health risks. Here, we report an update of North American activity patterns before and after pandemic onset, and implications to radioactive radon gas exposure, a leading cause of lung cancer. We surveyed 4009 Canadian households home to people of varied age, gender, employment, community, and income. Whilst overall time spent indoors remained unchanged, time in primary residence increased from 66.4 to 77% of life (+ 1062 h/y) after pandemic onset, increasing annual radiation doses from residential radon by 19.2% (0.97 mSv/y). Disproportionately greater changes were experienced by younger people in newer urban or suburban properties with more occupants, and/or those employed in managerial, administrative, or professional roles excluding medicine. Microinfluencer-based public health messaging stimulated health-seeking behaviour amongst highly impacted, younger groups by > 50%. This work supports re-evaluating environmental health risks modified by still-changing activity patterns.